When "Nice" Isn't: Confronting Niceness and Whiteness to Center Equity in Teacher Education. (3rd April 2023) - Gardiner, Wendy; Hinman, Tierney B.; Tondreau, Amy; Degener, Sophie; Dussling, Tess M.; Stevens, Elizabeth Y.; Wilson, Nance S.; White, Kristen
ABSTRACT: Niceness is a socialized disposition, particularly amongst white women, that prioritizes comfort and neutrality while preventing resistance against oppressive systems. Given the demographics of teachers and teacher educators, niceness and whiteness are deeply embedded in programs and institutions. As eight white, female teacher educators, we drew on the power of cross-institutional collaboration to form a self-study community of practice with the purpose of interrogating and dismantling the ways niceness and whiteness function in our teaching and teacher institutions and create barriers to centering equity and justice. Findings indicated that collaboration helped us identify how niceness shaped and continues to shape our teaching and teacher identities, particularly how we navigate difficult conversations, think about our roles as teacher educators, and imagine literacy curricula. Findings also indicated that despite efforts to recognize and interrupt niceness and whiteness, our growth was nonlinear, and we find that constant vigilance and reflection is necessary. Implications for the broader field of education include the power of self-study for disrupting niceness and whiteness in teacher education and orienting the community toward action through mutual support and accountability, while also recognizing the ways in which niceness continues to function as a barrier for enacting change for social justice.